SINERGITAS TAX CENTER DAN DIREKTORAT JENDERAL PAJAK DALAM PERSPEKTIF PSIKOLOGI KOMUNIKASI DAN PERENCANAAN PROGRAM KOMUNIKASI - Yeni Nuraeni; Beny Susanti; Sugiharti Binastuti; Diana Sari (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The purpose of this study is to find out that the synergy between the Directorate General of Taxes and the Tax Center can increase tax awareness for taxpayers in Indonesia, especially in the Depok area, West Java. This study uses a qualitative methodology with a communication psychology approach and communication program planning. Synergy of Gunadarma University Tax Center and Directorate General of Taxes (KPP Pratama Depok) succeeded in facilitating the needs of taxpayers in realizing orderly tax reporting and paying taxes. The synergy of the Gunadarma University Tax Center and KPP Pratama Depok succeeded in making taxpayers aware of the importance of reporting taxes by seeing determination as an implementation of reinforcement of response in communication psychology. The success of this synergy can be seen from the trend of tax reports that have been successfully collected by KPP Pratama Depok in the last 3-5 years in collaboration with the Gunadarma University Tax Center.